2010
DOI: 10.1158/1055-9965.epi-10-0230
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Breast Cancer in the Me-Can (Metabolic Syndrome and Cancer) Project

Abstract: Background: Few studies have assessed the metabolic syndrome (MetS) as an entity in relation to breast cancer risk, and results have been inconsistent. We aimed to examine the association between MetS factors (individually and combined) and risk of breast cancer incidence and mortality.Methods: Two hundred ninety thousand women from Austria, Norway, and Sweden were enrolled during 1974-2005, with measurements of height, weight, blood pressure, and levels of glucose, cholesterol, and triglycerides. Relative ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
141
3
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(158 citation statements)
references
References 39 publications
9
141
3
5
Order By: Relevance
“…The Madena software calculated the size of this dense area in cm 2 . Absolute mammographic density represented the number of the tinted pixels.…”
Section: Assessment Of Mammographic Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…The Madena software calculated the size of this dense area in cm 2 . Absolute mammographic density represented the number of the tinted pixels.…”
Section: Assessment Of Mammographic Densitymentioning
confidence: 99%
“…1), although the findings are somewhat contradictory (2,3). Low levels of HDL-C, which transport and store cholesterol (4), have been associated with low-grade inflammation and proinflammatory cytokines (5-7), which may stimulate breast cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity may increase breast cancer risk through a number of different mechanisms including insulin resistance, the metabolic syndrome, increased production of sex hormones, insulin-like growth factors, chronic low-grade inflammation and alterations in adipokines [9,[11][12][13][14][15]. These biological pathways, in turn, are the hypothesised targets through which physical activity may exert its protective effects over breast cancer development [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the metabolic syndrome was also found associated with a decreased risk of incident BC in women below age 50 with high body mass index (BMI), and with an increased risk of BC mortality in women of ages above 60, according to a European study (Bjørge et al, 2010). New evidence emphasizes that metabolic syndrome increases the risk mainly in postmenopausal women (Capasso et al, 2011) and it has been found as significantly more prevalent in triple-negative BC patients as opposed to non-triple-negative patients (Maiti et al, 2010).…”
Section: Introductionmentioning
confidence: 99%